Earthworm species in Musa spp. plantations in Brazil and worldwide - Cremonesi, Marcus Vinicius; Santos, Alessandra; Rozane, Danilo Eduardo [UNESP]; Carolina Bartz, Marie Luise; Brown, George Gardner (Pensoft Publishers, 2021)
Bananas and plantains are major commodity/food crops that represent an important habitat for earthworms, although so far, no review is available on earthworm communities associated with banana/plantain crops worldwide. The Vale do Ribeira region is among the largest banana producing areas in Brazil, but little is known of the earthworms living there. Hence, the present study assessed earthworm populations and species in three banana plantations and adjacent Atlantic forest fragments along the Ribeira de Iguape River using standard (hand sorting) methodologies. Furthermore, we review earthworm populations reported in banana/plantain plantations worldwide. Only two species (Pontoscolex corethrurus, Amynthas gracilis) belonging to two families (Rhinodrilidae, Megascolecidae) were found in the Ribeira River valley, occurring concurrently. Abundance was low (< 13 indiv. m(-2)) compared with other banana plantations worldwide, that frequently surpassed 100 indiv. m(-2). More than 70 studies reported earthworms from >200 banana plantations in 28 countries, and mean species richness was 2.7 per site, ranging from 1 to 10 species. Exotics predominated in most sites and P. corethrurus was the most prevalent species encountered. Overall, more than 104 species from 10 families were reported, with around 61 native and 43 exotic widespread species, mainly of the Megascolecidae, Lumbricidae and Acanthodrilidae families. Richness was highest in India (27 spp.) and the Canary Islands (25 spp.), but native species dominated only in a few countries and sites, while exotics were prevalent especially in island countries and Brazil. Lower-input practices appear to be important for earthworm communities and banana plantations can have large earthworm populations in some cases, which may be contributing to soil processes and plant production, topics that deserve further attention. However, many important banana-producing countries have not yet been evaluated, so further work is warranted, both in terms of applied ecology and biodiversity.
Keywords: Annelida; banana; biodiversity; Oligochaeta; plantain; Pontoscolex corethrurus